Field Test Research on the Downhole Multiphysics Micro-Measurer Based on the MEMS Microchip - Li, Mu; Liu, Wei; Zhang, Hengrui; Tang, Chunjing; Fu, Jiasheng; Zhai, Xiaoqiang; Wang, Hao (Frontiers in Earth Science, 2023)
Since Pressure While Drilling (PWD) has the disadvantages of single point measurement and high cost of application, a micro measurer based on MEMS (Micro-electromechanical Systems) sensor technology, which can measure downhole temperature, pressure, magnetic field and dynamic signal, has been developed to achieve real-time, efficient and accurate measurement of multiple parameters in the well. The kernel circuit system is the core of measurement and control, and the shell plays the role of protecting the kernel circuit. The shell of the micro-measurer is made of preferably selected materials with high temperature and pressure resistance, corrosion resistance, small size and low density, which can adapt to work in drilling fluid for a long time. The micro-measurer uses integrated interfaces on the shell to enable communication between the host computer and the measuring machine. Based on the field test, both the functional integrity and data measurement accuracy of the micro-measurer are verified. Via analysis of the measured data, the profile of the downhole temperature field is constructed. The physical phenomena reflected by the measured magnetic field signal and dynamic signal are consistent with the actual working conditions observed in the test. Hence, as a new microchip measuring device, the micro-measurer can better serve the drilling engineering field and provide technical support for real-time measurement of downhole parameters in the future.